PENGARUH PENAMBAHAN GULA PASIR TERHADAP WAKTU IKAT AWAL PASTA SEMEN DAN MORTAR - Retno Trimurtiningrum; Sutriono, Bantot; Arrowrichta, Billy; Watu, Hiasintus Bertus (Institut Teknologi Nasional Yogyakarta, 2019)
In concrete construction process, it is often happened that the location of batching plan is different from the project location, so it takes time in its material transport. To prevent the concrete material from early setting time before casting, it is necessary to add chemical admixture to slow the setting time, which is retarder. Generally, chemical admixtures including retarder have relatively expensive price. Therefore, this study used alternative material such as sugar, because sugar is one of retarder’s consituent material that has relatively low price and also easy to obtain. The percentage of sugar in this research were 0% (as a control specimen); 0.03%; 0.05% and 0.1%. The setting time test used the Vicat neddle apparatus for cement paste and penetration resistance tools for mortar. The setting time result shows that sugar can delay the initial setting time on cement paste or mortar specimens. The longest initial setting time was obtained by a mixture that has been added 0,1% of sugar which is 157,69 minutes for cement paste test and 250 minutes for mortar specimen.